Disruption of adeB gene has a greater effect on resistance to meropenems than adeA gene in Acinetobacter spp. isolated from University Malaya Medical Centre. - Wong, E.W.; Yusof, M.Y.; Mansor, M.; Anbazhagan, D.; Ong, S.Y.; Sekaran, S.D. (2009)
INTRODUCTION: The AdeABC pump of Acinetobacter spp. confers resistance to various antibiotic classes. This pump is composed of the AdeA, AdeB, and AdeC proteins where AdeB is a member of the resistance-nodulation-division efflux pump superfamily. The adeA, adeB, and adeC genes are contiguous and adjacent to adeS and adeR, which are transcribed in the opposite direction and which specify proteins homologous to sensors and regulators of two-component systems, respectively. In this study, an attempt is made to elucidate the role of the AdeABC efflux pump in carbapenem resistance in Acinetobacter spp. METHODS: 39 carbapenem-resistant clinical isolates of Acinetobacter spp. were used. Minimum inhibitory concentrations were evaluated using the agar dilution method according to Clinical and Laboratory Standards Institute standards. The presence of carbapenem hydrolysing oxacillinases and AdeABC efflux pump genes were determined by PCR amplification. Subsequently, each gene was inactivated by plasmid insertion in order to study the contribution of these genes in developing antibiotic resistance and the resulting mutants were tested for their antimicrobial susceptibilities. RESULTS: Among the multidrug-resistant strains, 36 strains had all the three (A, B, C) genes detected, while the remaining three strains had one or two of the genes detected. Inactivation of these individual genes showed decreased antimicrobial susceptibility indicating its contribution towards the development of antimicrobial resistance. CONCLUSION: The presence of AdeABC multidrug efflux pump plays a major role in the development of antimicrobial resistance in Acinetobacter spp. The presence of either one or an interplay between these genes may have an effect on antimicrobial resistance in Acinetobacter spp.